Microwave roasting of siderite and the catalytic combustion effects on anthracite. (5th May 2017) - Lin, Guo; Zhang, Libo; Peng, Jinhui; Hu, Tu; Yang, Li
Highlights: Siderite is roasted by microwave heating with different holding times at 800 °C. Roasting products are employed as catalyst to investigate the catalytic combustion effects on anthracite. The reasons of combustion rate decline and catalytic mechanism are investigated and analyzed. Abstract: Microwave roasting of siderite at 800 °C with different holding times and the catalytic combustion effects on anthracite are investigated. The heating rate curves indicate that siderite can be heated in microwave field, and the heating rate increases considerably when FeCO3 almost decomposes and oxidizes to Fe3 O4 and Fe2 O3 . The combustion rate increases by 31.74% with 0.5% roasting products of siderite as catalyst at a holding time of 40 min using microwave roasting. The Fe2 O3 content in roasting products increases with microwave holding time. The size distribution results indicate that small particles cluster together and the amount of large particles increases with holding time, thereby the decreasing catalytic effect on anthracite at holding time above 40 min. The thermogravimetric-derivative thermogravimetric (TG-DTG) analysis results indicate that ignition temperature, combustion reactivity and burnout index significantly improve with catalyst addition. Differential scanning calorimeter (DSC) analysis results show that heat release of anthracite with catalyst increases by 10.09% compared with that of raw-anthracite.